Comparison of neoadjuvant chemotherapy response and prognosis between HR-low/HER2-negative BC and TNBC: an exploratory real-world multicentre cohort study - Peng, Jing; Hong, Yue; Chen, Qitong; Xu, Feng; Zhang, Danhua; Yao, Jia; Zou, Qiongyan; Yuan, Liqin; Li, Lun; Long, Qian; Liao, Liqiu; Liu, Mingwen; et al. (Frontiers in Endocrinology, 2024)
Objective: Hormone receptor (HR)-low/HER2-negative breast cancers (BCs) are more likely to be basal-like BCs, with similar molecular features and gene expression profiles to HR-negative (estrogen receptor <1% or negative and progesterone receptor <1% or negative) BCs. Recently, with the clinical application of adjuvant intensive therapy for triple-negative breast cancer (TNBC), the prognosis of TNBC patients without pathological complete response (pCR) has significantly improved. Therefore, it is necessary to reanalyse the prognostic characteristics of clinically high-risk HR-low/HER2-negative BC.According to the inclusion and exclusion standards, 288 patients with HR-low/HER2-negative BC and TNBC who received NAC and were followed up between 2015 and 2022 at three breast centres in Hunan Province, China, were enrolled. Inverse probability of treatment weighting (IPTW) was utilized to mitigate imbalances in baseline characteristics between the HR-low/HER2-negative BC group and TNBC group regarding event-free survival (EFS) and overall survival (OS). The primary clinical endpoints were pCR and EFS, while the secondary endpoints included OS, objective response rate (ORR), and clinical benefit rate (CBR).The pCR rate (27.1% vs. 28.0%, P = 1.000), ORR rate (76.9% vs. 78.3%, P = 0.827) and CBR rate (89.7% vs. 96.5%, P = 0.113) after NAC were similar between the HR-low/HER2-negative BC and the TNBC group. EFS in patients with non-pCR from the 2 groups was significantly inferior in comparison to patients with pCR (P = 0.001), and the 3-year EFS was 94.74% (95% CI = 85.21% to 100.00%) and 57.39% (95% CI =43.81% to 75.19%) in patients with pCR and non-pCR from the HR-low/HER2-negative BC group, respectively, and 89.70% (95% CI = 82.20% to 97.90%) and 69.73% (95% CI = 62.51% to 77.77%) in the TNBC patients with pCR and non-pCR, respectively.In the real world, the therapeutic effects of NAC for HR-low/HER2-negative BCs and TNBCs were similar. EFS of patients with non-pCR in the HR-low/HER2-negative BC group was inferior to that of the TNBC group with non-pCR, suggesting that it is necessary to explore new adjuvant intensive therapy strategies for these patients.